A Performance Model for MSMEs Based on Access to Financing and Its Impact on Community Welfare in Deli Serdang Regency - Tyus Windi Ayuni; Rafida Khairani; Debora Tambunan; Mega Sanjaya; Darwan Tanady (Journal of Business Integration Competitive, 2026)
This study aims to analyze the effect of access to financing on community welfare, with the performance of Micro, Small, and Medium Enterprises (MSMEs) serving as a mediating variable in Deli Serdang Regency. This study employs an explanatory research approach. The sample consists of 93 MSMEs in Deli Serdang Regency. A quantitative approach is applied using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). Data were collected through the distribution of questionnaires to MSME operators as research respondents. The results indicate that access to financing has a positive and significant effect on MSME performance. Furthermore, MSME performance also has a positive and significant effect on community welfare. In addition, access to financing also has a direct positive and significant effect on community welfare. The results of the mediation test indicate that MSME performance mediates the relationship between access to financing and community welfare. These findings suggest that improved access to financing, accompanied by enhanced MSME performance, can make a significant contribution to increasing community welfare. Therefore, the government and financial institutions need to play an active role in expanding access to financing and improving MSME capacity in order to enhance business performance and community welfare in a sustainable manner.